Single-cell RNA sequencing reveals differential expression of EGFL7 and VEGF in giant-cell tumor of bone and osteosarcoma. Issue 14 (July 2022) - Feleke, Mesalie; Feng, Wenyu; Song, Dezhi; Li, Hengyuan; Rothzerg, Emel; Wei, Qingjun; Kõks, Sulev; Wood, David; Liu, Yun; Xu, Jiake
Dysregulation of angiogenesis is associated with tumor development and is accompanied by altered expression of pro-angiogenic factors. EGFL7 is a newly identified antigenic factor that plays a role in various cancers such as breast cancer, lung cancer, and acute myeloid leukemia. We have recently found that EGFL7 is expressed in the bone microenvironment, but its role in giant-cell tumor of bone (GCTB) and osteosarcoma (OS) is unknown. The aims of this study are to examine the gene expression profile of EGFL7 in GCTB and OS and compare with that of VEGF-A-D and TNFSF11 using single-cell RNA sequencing data. In-depth differential expression analyses were employed to characterize their expression in the constituent cell types of GCTB and OS. Notably, EGFL7 in GCTB was expressed at highest levels in the endothelial cell (EC) cluster followed by osteoblasts, myeloid cells, and chondrocytes, respectively. In OS, EGFL7 exhibited highest expression in EC cell cluster followed by osteoblastic OS cells, myeloid cells 1, and carcinoma associated fibroblasts (CAFs), respectively. In comparison, VEGF - A is expressed at highest levels in myeloid cells followed by OCs in GCTB, and in myeloid cells, and OCs in OS. VEGF - B is expressed at highest levels in chondrocytes in GCTB and in OCs in OS. VEGF - C is strongly enriched in ECs and VEGF-D is expressed at weak levels in all cell types in both GCTB and OS. TNFSF11 (or RANKL) shows high expression in CAFs and osteoblastic OS cells in OS, and osteoblasts in GCTB. This study investigates pro-angiogenic genes in GCTB and OS and suggests that these genes and their expression patterns are cell-type specific and could provide potential prognostic biomarkers and cell type target treatment for GCTB and OS.